TECHNICAL CHARACTERISTICS OF THE USE OF VIBRATING CONVEYORS FOR DRYING ROSA CANINAS - Mamatusmonova, Dilnoza; Mamatov, Sherzod (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2025)
The article examines the advantages of drying Rosa canina fruits using a drying technology with 3-stage vibrating conveyors. According to the research results, the use of 3-stage vibrating conveyors in the convective method reduces drying time, energy consumption, and vitamin C loss by up to 17%. Also, the organoleptic indicators of the product and the overall quality level have improved.